(untitled) (INNOVATIVE ECONOMY, 2025)
Svynous I.V., Turzhanskyi V.A., Khoma D.M. ACCOUNTING AS A TOOL FOR FINANCIAL LITERACY: CHALLENGES FOR ECONOMIC EDUCATION Purpose. The aim of the article is to determine the role of accounting in the formation of financial literacy, to substantiate its importance for personal and professional development, and to outline the main challenges facing economic education in Ukraine in the process of integration into the global educational and economic space. Methodology of research. The article uses a bunch of general scientific and special methods of cognition. Methods of analysis and synthesis are used to reveal the essence of accounting as a tool for building financial literacy and figuring out its place in the economic education system. The comparative method made it possible to compare international and domestic experience in teaching accounting disciplines and integrating them into educational programmes. A structural and logical approach was used to systematise contemporary challenges and trends in the development of accounting education. In addition, elements of statistical analysis and content analysis of educational documents and scientific publications were used to assess the effectiveness of educational practices in the context of improving financial literacy. Findings. The study showed that accounting is an important tool for developing financial literacy, as it provides practical knowledge of financial management and economic decision-making. It was found that the integration of accounting disciplines into educational programmes increases students’ ability to navigate financial flows and critically evaluate economic information. A comparison of international and Ukrainian experience indicates the need to adapt educational practices to the requirements of the globalised market. It has been established that the key challenges remain the digitisation of accounting, updating the content of disciplines and preparing teachers for new educational approaches. Overall, the results confirm that the modernisation of accounting education is a necessary condition for improving the financial literacy of young people and strengthening economic education in Ukraine. Originality. The article substantiates for the first time the role of accounting as a systemic tool for improving the financial literacy of students of economics. An integrative approach is proposed, which involves combining traditional accounting disciplines with digital technologies and innovative educational practices. The essence of financial literacy in the context of economic education is clarified, with an emphasis on practical competencies in the analysis and management of financial flows. Specific challenges for the Ukrainian higher education system related to adaptation to international standards and digitalisation are identified. The conceptual foundations for improving accounting curricula as a basis for increasing the competitiveness of graduates in the global labour market are formulated. It was found that the key challenges remain the digitalization of accounting, updating the content of disciplines, and training teachers for new educational approaches. Overall, the results confirm that the modernization of accounting education is a necessary condition for increasing the financial literacy of young people and strengthening economic education in Ukraine. Practical value. The obtained results have practical significance for improving accounting curricula in higher education institutions with an economic profile. The proposed approaches can be used in the development of courses and teaching materials aimed at developing students’ financial literacy. The results can be used by teachers, university administrations and educational policy bodies to improve the quality of economic education. Key words: accounting; financial literacy; economic education; accounting training; digitalisation; educational programmes; competencies; financial stability.